Soluble CD13 induces inflammatory arthritis by activating the bradykinin receptor B1 - Pei-Suen Tsou; Chenyang Lu; Mikel Gurrea-Rubio; Sei Muraoka; Phillip L. Campbell; Qi Wu; Ellen N. Model; Matthew E. Lind; Sirapa Vichaikul; Megan N. Mattichak; William D. Brodie; Jonatan L. Hervoso; et al. (The Journal of Clinical Investigation, 2022)
CD13, an ectoenzyme on myeloid and stromal cells, also circulates as a shed, soluble protein (sCD13) with powerful chemoattractant, angiogenic, and arthritogenic properties, which require engagement of a G protein–coupled receptor (GPCR). Here we identify the GPCR that mediates sCD13 arthritogenic actions as the bradykinin receptor B1 (B1R). Immunofluorescence and immunoblotting verified high expression of B1R in rheumatoid arthritis (RA) synovial tissue and fibroblast-like synoviocytes (FLSs), and demonstrated binding of sCD13 to B1R. Chemotaxis, and phosphorylation of Erk1/2, induced by sCD13, were inhibited by B1R antagonists. In ex vivo RA synovial tissue organ cultures, a B1R antagonist reduced secretion of inflammatory cytokines. Several mouse arthritis models, including serum transfer, antigen-induced, and local innate immune stimulation arthritis models, were attenuated in Cd13–/– and B1R–/– mice and were alleviated by B1R antagonism. These results establish a CD13/B1R axis in the pathogenesis of inflammatory arthritis and identify B1R as a compelling therapeutic target in RA and potentially other inflammatory diseases.